Who Cares if Parents have Unpredictable Work Schedules?: Just-in-Time Work Schedules and Child Care Arrangements. (14th September 2020) - Harknett, Kristen; Schneider, Daniel; Luhr, Sigrid
Abstract: Working parents must arrange some type of care for their young children when they are away at work. For parents with unstable and unpredictable work schedules, the logistics of arranging care can be complex. In this paper, we use survey data from the Shift Project, collected in 2017 and 2018 from a sample of 3, 653 parents who balance work in the retail and food service sector with parenting young children from infants to nine years of age. Our results demonstrate that unstable and unpredictable work schedules have consequences for children's care arrangements. We find that parents' exposure to on-call work and last-minute shift changes are associated with more numerous care arrangements, with a reliance on informal care arrangements, with the use of siblings to provide care, and with young children being left alone without adult supervision. Given the well-established relationship between quality of care in the early years and child development, just-in-time scheduling practices are likely to have consequences for children's development and safety and to contribute to the intergenerational transmission of disadvantage.